Comparison of different strategies for nitrogen removal by simultaneous nitrification and denitrification process in a batch rotating disk reactor - Miranda Zoppas, Fernanda (2017)
In this paper, different strategies of aeration and organics feed in the reactor were studied toevaluate the simultaneous nitrification and denitrification (SND) process efficiency for a sequencing batchrotating disk biofilm reactor (SBRDR). The effect of C/N ratio on biological nitrogen removal was also studied.Among the four strategies used, the ones with organic feeding showed the best results to promote SND. It wasalso observed a different behavior: the efficiency of SND as a function of the C/N ratio shows a tendency to ahave a lower value than values previously reported in the literature. A continuous or intermittent aeration in theprocess did not improved the nitrogen removal. These results provide sufficient knowledge of the parametersthat have the most influence on the efficient nitrogen removal via SND in batch rotating disk reactors.Keywords: batch reactor,denitrification, nitrification, nitrogen removal, rotating disk.